1988
DOI: 10.1002/for.3980070304
|View full text |Cite
|
Sign up to set email alerts
|

The consistency, coherence and calibration of holistic, decomposed and recomposed judgemental probability forecasts

Abstract: In this paper we make an empirical investigation of the relationship between the consistency, coherence and validity of probability judgements in a real-world forecasting context. Our results indicate that these measures of the adequacy of an individual's probability assessments are not closely related as we anticipated. Twenty-nine of our thirty-six subjects were better calibrated in point probabilities than in odds and our subjects were, in general more coherent using point probabilities than odds forecasts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…However, the lack of information availability might offset this advantage. Although this method has been suggested for forecasting tasks (Jones, Wheeler, Appan, & Saleem, 2006;Wright, Saunders, & Ayton, 1988), its applicability to the specific case of demand forecasting has not been tested.…”
Section: Comparison Of Integration Methodsmentioning
confidence: 99%
“…However, the lack of information availability might offset this advantage. Although this method has been suggested for forecasting tasks (Jones, Wheeler, Appan, & Saleem, 2006;Wright, Saunders, & Ayton, 1988), its applicability to the specific case of demand forecasting has not been tested.…”
Section: Comparison Of Integration Methodsmentioning
confidence: 99%
“…Unfortunately, there is little empirical evidence available to answer this question. Wright et al (1988) found that calibration of unions, intersection and disjunctions of events which were mechanically recomposed from marginal and conditional assessments were no better calibrated than holistically judged forecast probabilities for the same events. Further, no significant correlation was found between the coherence and the subsequent calibration of the assessed probabilities.…”
Section: Decomposition-recompositionmentioning
confidence: 98%
“…Depending on which metric is used, the judge's task of turning subjective feelings of uncertainty into measurable/usable numeric estimates can be either helped or hindered. For example, Wright et al (1988) found that for a short-term forecasting task of impersonal events (e.g. "will the pound fall below one dollar in the next 2 months?…”
Section: Some Influences On the Assessed Quality Of Judgementmentioning
confidence: 99%
“…That is, assigned probabilities generally exceed the proportion of judgments that turn out to be correct (for reviews, see Lichtenstein, Fischhoff, & Phillips, 1982;Yates, 1990). This bias has been observed on a wide variety of tasks involving general knowledge (e.g., Koriat, Lichtenstein, & Fischhoff, 1980;Paese & Feuer, 1991;Yates et at., 1989), interpersonal judgment (e.g., Dunning, Griffin, Milojkovic, & Ross, 1990;Paese & Kinnaly, 1991), and forecasts of personal events (e.g., Hoch, 1985;Vallone, Griffin, Lin, & Ross, 1990;Wright & Ayton, 1989), and impersonal events (e.g., Fischhoff & MacGregor, 1982;Wright, Saunders, & Ayton, 1988). Although there are some exceptions to this bias (see Keren, 1987;Murphy & Winkler, 1984), there is little reason to believe that peers are any less prone to overconfidence when sharing their judgments on difficult matters.…”
Section: (Un)biased Confidencementioning
confidence: 99%